Art market and connoisseurship : a closer look at paintings by Rembrandt, Rubens and their contemporaries - Tummers, Anna; Jonckheere, Koenraad (Amsterdam studies in the Dutch golden age., 2008)
This essential volume traces the evolution of connoisseurship in the booming art market of the seventeenth- and eighteenth centuries. Not to be missed by anyone with an interest in the Old Masters and the early modern art market.